A = ( x² - 2 × x ×2 +2²) - ( 5x +3) ( x -2)
A= ( x- 2)² - ( 5x +3) ( x -2)
B = x (3x -12) + ( x² - 4²)
B = x ( 3x -12) + (x+4) ( x -4)
C = ( x² - √7² ) - 5x(x +√7)
C = (x +√7) ( x - √7) - 5x(x+√7)
C= ( x+√7) ( x-√7 - 5x )
C = (x+√7 ) ( -4x -√7)
D = ( x +√8) (x - √8) + 3x( x² + 2²)
D= (x+√8) ( x - √8) + 3x [ ( x+2) (x -2) ]
H = x² - 2 × 2 × x + 2² + 4 ( [tex] \frac{4}{4} + \frac{x}{4} - \frac{2}{4} )[/tex]
H= (x - 2)² + 4( 4 +x -2)
H= (x -2)² + 4 ( 2+x) .
Désolée , j'ai pas fait les autres , j'ai pas encore étudié ça! !! .